PATRIMONIO ESPAÑOL, CINE ESPAÑOL. EL EXTRAÑO CASO DE JUANA LA LOCA (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
(…)This essay projects on the Spanish film Juana la loca interpretive categories derived from the study of British historical films such as Elizabeth. It finds in Juana la loca a variant of the tension between the progressivism of narrative content and the reactionary aesthetic form typical of this British film subgenre. This specific film form is a symptom that reveals a great deal about Spanish cultural contradictions at the time (…)